Pathogenic variants in EP300 and ANKRD11 in patients with phenotypes overlapping Cornelia de Lange syndrome. Issue 7 (31st May 2020) - Cucco, Francesco; Sarogni, Patrizia; Rossato, Sara; Alpa, Mirella; Patimo, Alessandra; Latorre, Ana; Magnani, Cinzia; Puisac, Beatriz; Ramos, Feliciano J.; Pié, Juan; Musio, Antonio
Abstract: Cornelia de Lange syndrome (CdLS), Rubinstein–Taybi syndrome (RSTS), and KBG syndrome are three distinct developmental human disorders. Variants in seven genes belonging to the cohesin pathway, NIPBL, SMC1A, SMC3, HDAC8, RAD21, ANKRD11, and BRD4, were identified in about 80% of patients with CdLS, suggesting that additional causative genes remain to be discovered. Two genes, CREBBP and EP300, have been associated with RSTS, whereas KBG results from variants in ANKRD11 . By exome sequencing, a genetic cause was elucidated in two patients with clinical diagnosis of CdLS but without variants in known CdLS genes. In particular, genetic variants in EP300 and ANKRD11 were identified in the two patients with CdLS. EP300 and ANKRD11 pathogenic variants caused the reduction of the respective proteins suggesting that their low levels contribute to CdLS‐like phenotype. These findings highlight the clinical overlap between CdLS, RSTS, and KBG and support the notion that these rare disorders are linked to abnormal chromatin remodeling, which in turn affects the transcriptional machinery.